Design an ideal biodegradable polymer - Lau, Kai Xiang. (2010)
The pollution problem caused by the accumulation of plastics in disposal sites is an imminent issue that has to be resolved swiftly. As such, there is an increasing need for research and development in environmentally degradable polymers. This report discusses the four basic types of environmentally degradable polymers: biodegradable polymers, photodegradable polymers, oxidatively degradable polymers and hydrolytically degradable polymers. Additives such as Totally Degradable Polymer Additive (TDPA) which aids in the rate of degradation of polymers will be discussed. Other methods to reduce the polymer waste, such as the up-cycling of PET to form biodegradable polymers, will also be presented in this report. In addition, this report will discuss factors that affect the degradation rates of environmentally degradable polymers. At the end of the report, the author will attempt to create his own version of an ideal environmentally degradable polymer which fits all the degradation criteria as presented in the report.